2021
DOI: 10.3390/antibiotics10030247
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Extended-Spectrum β-Lactamase (ESBL)-Encoding Genes among Multidrug-Resistant Gram-Negative Pathogens Collected from Three Different Countries

Abstract: The incidence of Extended-spectrum β-lactamase (ESBL)-encoding genes (blaCTX-M and blaTEM) among Gram-negative multidrug-resistant pathogens collected from three different countries was investigated. Two hundred and ninety-two clinical isolates were collected from Egypt (n = 90), Saudi Arabia (n = 162), and Sudan (n = 40). Based on the antimicrobial sensitivity against 20 antimicrobial agents from 11 antibiotic classes, the most resistant strains were selected and identified using the Vitek2 system and 16S rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…As in our study, findings regarding genetic diversity in isolates have varied among researchers [69][70][71][72]. Additionally, the PFGE results in the present study revealed no specific pattern of association between pulsotype cluster analyses and the resistant phenotypes of the isolates, which may be a reflection of the genomic characteristics of this Gram-negative opportunistic pathogen in which the plasmid genome and chromosomal genes are large (as previously documented [59]). It is possible that MDR could be more plasmid-based than chromosomal.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…As in our study, findings regarding genetic diversity in isolates have varied among researchers [69][70][71][72]. Additionally, the PFGE results in the present study revealed no specific pattern of association between pulsotype cluster analyses and the resistant phenotypes of the isolates, which may be a reflection of the genomic characteristics of this Gram-negative opportunistic pathogen in which the plasmid genome and chromosomal genes are large (as previously documented [59]). It is possible that MDR could be more plasmid-based than chromosomal.…”
Section: Discussionsupporting
confidence: 58%
“…Polyclonal ESBL-KP was also reported [ 58 ] in a non-outbreak hospital environment and was attributed to possible importation into hospital settings. Generally, the numbers of ESBL-producing bacterial pathogens have increased in the past few decades, with geographical and regional disparity [ 59 ]. Thus, K. pneumoniae isolates such as those in this report pose immense challenges to clinicians in the management of multidrug-resistant infections by these isolates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent surveillance of resistant pathogens in Egypt, Sudan, and Saudi Arabia revealed the ratios of the multidrugresistant strains as 74.4%, 90.1%, and 97.5%, respectively. E. coli and K. pneumoniae were the most resistant to macrolides followed by penicillins and cephalosporin, while P. aeruginosa showed the highest resistance to penicillins followed by classes that varied among different countries [44]. Nevertheless, this potent opportunistic pathogen has a common virulence and adaptation regulatory system that operates in environmental and clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…In Mediterranean countries, an endemic prevalence of multidrug-resistant K. pneumoniae (MDR-KP) has been recorded [1] and, as a part of this area, Egypt has witnessed a significant spread of MDR-KP with several reports being issued [2,3]. What renders the problem more complicated is that the proper treatment choice for MDR-KP infections is not well determined yet, thus, making the control of such infections a serious challenge for healthcare professionals [4].…”
Section: Introductionmentioning
confidence: 99%
“…Expanded-spectrum cephalosporins are still among the most globally prescribed antimicrobial agents [5]. This extensive usage has been mirrored by a global expansion of extended-spectrum β-lactamase (ESBL)-producing K. pneumoniae showing resistance to ceftriaxone, cefotaxime, ceftazidime, and monobactams (as aztreonam), reaching 50% in some countries [4,6]. At a national level, a surveillance study carried out in five hospitals in Cairo, from 1999 to 2000, showed reduced susceptibility of Klebsiella spp.…”
Section: Introductionmentioning
confidence: 99%